PENGARUH CONSUMER-BASED BRAND EQUITY THE COFFEE BEAN & TEA LEAF SURABAYA ATAU MAXX COFFEE SURABAYA TERHADAP CUSTOMER SATISFACTION DAN BRAND LOYALTY MENURUT PELANGGAN SURABAYA - Darwis Saputra Laurianto; Indarini Indarini; Silvia Margaretha (CALYPTRA, 2018)
This study investigates the effect of the brand equity on the customer satisfaction and the brand loyalty of The Coffee Bean & Tea Leaf or Maxx Coffee coffee shop’s customers. The Coffee Bean & Tea Leaf is the strongest competitor of Maxx Coffee. The results of this study found that staff behaviour, ideal self-congruence, and lifestyle-congruence are factors that have a significant positive effect on customer satisfaction at The Coffee Bean & Tea Leaf. Physical quality and brand identification are factors that have no significant effect on customer satisfaction at The Coffee Bean & Tea Leaf. Physical quality and staff behavior are factors that have a significant positive effect on customer satisfaction at Maxx Coffee. Ideal self-congruence, brand identifcation, andlifestyle-congruenceare factors that have no significant effect on customer satisfaction at Maxx Coffee. However, in both of The Coffee Bean & Tea Leaf and Maxx